Silica gel doped with cobalt oxide prepared by sol-gel technique; improving dielectric charge storage - Abd El Hamid, R.K.; Battisha, I. K.; Shahin, N.A.M (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The structural, morphology and magnetic properties of Cobalt oxide embedded in silica gel with 10 mol. %, in monolith form, sintered at different temperature ranging from 60 up to 1300ºC, respectively recorded as (SC(60-1300) were prepared by a modified sol gel technique. The sintering temperature effect on the crystallization, surface morphology and magnetic behaviors of the prepared samples will be study, Phase identification by using surface morphology and X-ray diffraction will be study by using Transmission electron microscope (TEM) and Field emission scanning electron microscope imaging (FESEM). The nano-scale presence and the formation of the α-cristobalyte tetragonal phase of silica gel as well as the doped samples with cobalt oxide crystallinity enhancement were detected using the mentioned techniques. FTIR spectra were being study. The saturation magnetization (Ms), remnant magnetization (Mr) and coercive force (Hc), was founded to be equl to 0.183,0.031 emu/g and 46.7Oe respectively. The A. C. conductivity increased by increasing the temperature .Therefore, by increasing the sintering temperature of the silica gel network doped withCo3O4are applicant for several electronic and industrial devices with improved dielectric charge storage capacity and strength.